Documentation of a Numismatic Collection from the Period of the Roman Empire Using the Photogrammetry Method - Rybenská, Klára; Borůvková, Barbora; Burianová, Klára (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2024)
The article describes the possibilities of 3D documentation of historical monuments by photogrammetry on a selected sample of coins. It applies this selected method, verifies its suitability and describes some other digitization methods. It also contains a basic description of the methodology of creating 3D models of ancient coins.
Keywords: Photogrammetry; Numismatics; Digital Humanities; 3D; Memory Institutions